Estratégia competitiva e cultura organizacional: um estudo exploratório do estágio atual da indústria brasileira de equipamentos mecânicos pesados - Degenhardt, Victor Werner (2006)
The objective of this study is to explore, to identify and to analyze alignments in competitive strategies and organizational culture in Brazilian companies producing heavy machinery equipment. Scholar reference used to identify competitive strategies was Miles and Snow`s (2003), for organizational culture it was the Competitive Values Model by Quinn and Rohrbaugh (1983), and for the synchrony between the two of them it was the model by Quinn and Grath (1985). The basic assumption is that culture, with its power to move members toward a common purpose, is capable of rolling out competencies to other members, thus helping to implement a competitive strategy. Certain types of organizational culture would be better tuned to certain strategic characteristics, thus favoring their alignment. Field research was based on the methodology of multiple-case studying, involving seven large corporations and seven small and medium sized companies from the heavy machinery industry. Investigation was quantitative by means of questionnaires, complemented by face to face interviews. The research indicates that the great majority of the companies studied have a defensive competitive strategy, a characteristic of the maturity of their sector. Their vision is conservative when developing new products, more concerned in improving efficiency to decrease costs and guarantee their market share. Most of the companies has presented a rational cultural, oriented according to their environment and centralizing decisions toward reaching their targets. Instrumental reasoning characterizes this sector in their struggle to show results to shareholders